Memoria y Universidad - Vallina, Carlos (Oficios Terrestres, 2015)
«Memory and university» is one of the chapters of the doctoral thesis of Carlos Vallina. As an academic memory addresses political and cultural contexts of the sixties and the seventies, and the Universidad Nacional de La Plata, as a fundamental part of this historical process of debates and political struggles, but with a look and perspectives of the present. Aesthetic forms of communication performance, in particular in the audiovisual field, are a way of knowing reality. The purpose of this test is a cross of days, structural coincidence of communicating a variety of forms and timelines fractured by the action of history, memory, emotions and the need to process a field of knowledge that gives meaning to everything.